Feed Mitigant Efficacy for Control of Porcine Epidemic Diarrhea Virus and Porcine Reproductive and Respiratory Syndrome Virus when Inoculated Alone or Together in Feed - C. Grace Elijah; Gage E. Nichols; Jordan T. Gebhardt; Cassandra K. Jones; Jason C. Woodworth; Steve S. Dritz; Jianfa Bai; Joe W. Anderson; Elizabeth G. Poulsen Porter; Aaron Singrey; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
Research has demonstrated that swine feed can be a fomite for viral transmission and feed additives can reduce viral contamination. Therefore, the objective of this study was to evaluate two feed additives in feed contaminated with PEDV or PRRSV. Feed additives included: no treatment, 0.33% commercial formaldehyde-based product, and 0.50% medium chain fatty acids (MCFA) blend. Feed samples were inoculated with PEDV and PRRSV alone or together at an inoculation concentration of 106TCID50/g for each virus. Once inoculated, feed was stored at room temperature for 24 h before analyzing via qRT-PCR. For samples inoculated with PEDV or PRRSV alone, a quantitative real time reverse transcription PCR (qRT-PCR) assay was used, which was designed to detect PEDV or PRRSV nucleic acid. For co-inoculated samples, an assay was designed to detect PEDV and PRRSV within a single assay. For PEDV alone, there was marginally significant evidence that feed additives resulted in differences in cycle threshold (Ct) value (P = 0.052), but no evidence was observed for pairwise differences. For PRRSV alone, formaldehyde increased Ct compared to the untreated control and MCFA treatment (P<0.05). For co-infection of PRRSV and PEDV, MCFA and formaldehyde increased Ct (P<0.05) in comparison to non-treated feed. In summary, formaldehyde increased Ct values in feed when contaminated with PRRSV while both feed additives increased Ct in feed when co-inoculated with PRRSV and PEDV. This study also provided evidence that the co-inoculation model can effectively evaluate mitigants.
Keywords: Porcine Epidemic Diarrhea Virus; Porcine Reproductive and Respiratory Syndrome Virus; Medium Chain Fatty Acids; Formaldehyde